The Influence of Turkish Cuisine in Romania - Gürsoy, Yüksel (Universitatea Transilvania Brasov, 2024)
Romania is a major country in southeastern Europe, located in the northern region of the Balkans. Due to Romania's proximity to Western European countries and the transit routes that reach them, various peoples have settled in Romanian lands since ancient times. Between 1400 and 1878, the Ottoman Empire ruled Romania. The Turks brought their unique cuisine along with the other customs and traditions to the places they conquered. In Romania, and particularly in the Dobruja region, we see the interplay of Turkish names in kitchenware and food and drink.
Keywords: Ottoman Cuisine; Turkish Cuisine; Romanian Cuisine; Gastronomy; Tourism